Conceptualizing Overdiagnosis in Cancer Screening - Marcus, Pamela M. (J Natl Cancer Inst, 2015)
The aim of cancer screening is to detect asymptomatic cancers whose treatment will result in extension of life, relative to length of life absent screening. Unfortunately, cancer screening also results in overdiagnosis, the detection of cancers that, in the absence of screening, would not present symptomatically during one’s lifetime. Thus, their detection and subsequent treatment is unnecessary and detrimental. This definition of overdiagnosis, while succinct, does not capture the ways it can occur, and our interactions with patients, advocates, researchers, clinicians, and journalists have led us to believe that the concept of overdiagnosis is difficult to explain and, for some, difficult to accept. We propose a dichotomy, the “tumor-patient” classification, to aid in understanding overdiagnosis. The tumor category includes asymptomatic malignant disease that would regress spontaneously if left alone, as well as asymptomatic malignant disease that stagnates or progresses too slowly to be life threatening in even the longest of lifetimes. The patient category includes asymptomatic malignant disease that would progress quickly enough to be life threatening during a lifetime of typical length, but lacks clinical relevance because death due to another cause intercedes prior to what would have been the date of symptomatic diagnosis had screening not occurred. Cancer screening of most organs is likely to result in overdiagnosis of both types. However, the ratio of tumor- to patient-driven overdiagnosis almost certainly varies, and may vary drastically, by organ, screening modality, patient characteristics, and other factors.